Impact of urinary microplastic exposure on cognitive function in primary school children - Donghan Zheng; Dan Wang; Shuo Zhang; Yan Liu; Qi Xi; Yang Weng (Ecotoxicology and Environmental Safety, 2025)
Microplastic (MP) contamination is a growing environmental concern, with potential implications for human health. Emerging evidence suggests that MPs may interfere with neurodevelopment. However, the association of urinary microplastic exposure on cognitive function in children remain poorly understood. This cross-sectional study aimed to assess the impact of urinary MPs exposure on cognitive development in 5670 primary school children (ages 7–10) from Shenyang, China. Microplastics, including polyamide (PA), polypropylene (PP), and polyvinyl chloride (PVC), were measured in urine samples, and cognitive development was evaluated using computerized tasks that assessed working memory and attention. Urinary microplastic levels varied widely, with median concentrations of 15 n/100 mL for total microplastics. Linear mixed-effects models revealed significant negative associations between higher urinary PA, PP, and total MPs exposure with reduced working memory performance (PA: β = −9.98, p < 0.001; PP: β = −4.95, p = 0.01). The association remained significant for superior working memory, with PP and PVC showing significant negative effects (PP: β = −1.77, p = 0.02; PVC: β = −2.05, p = 0.01). Additionally, total MPs exposure was associated with increased inattentiveness, as indicated by higher reaction time variability (β = −1.83, p = 0.04). Bayesian Kernel Machine Regression (BKMR) analysis revealed a dose-dependent negative association between urinary microplastics exposure and cognitive development, with higher exposure levels linked to impaired working memory in both the Two-Back and Three-Back tasks, while no consistent association was observed with inattentiveness (HRT-SE). Generalized Quantile-Weighted Sum (gQWS), and Quantile g-computation (g-comp) analyses further supported the findings, with g-comp models showing a stronger effect on working memory (β = −9.80, p < 0.01) and superior working memory (β = −2.35, p < 0.01). These results highlight the potential harmful effects of microplastic exposure on cognitive outcomes in children.